Sustaining multi-partner engaged research: principles, processes and tensions. Issue 4 (4th July 2019) - Singh, Kuki; Mildenhall, Paula; Roberts, Pauline; Wren, Julie
ABSTRACT: This paper presents a reflective analysis of a multi-partner, transdisciplinary research project where Nao humanoid robots were integrated into children's learning experiences at a community school. Using critical reflection as a method of inquiry principles of engaged research are conceptualised showing how they were articulated throughout the study, including how they were represented in the issues that characterised the project. A process of content analysis drawn from critical incidents told via a story-telling strategy revealed that the supportive and restrictive narratives that shaped our experience were embedded around the core principles of meeting community needs, reciprocity and boundary crossing. The complex and intersecting engagement processes necessitated skills in managing human and human-system relationships and interdependencies, temporal and spatial connections, social ecologies, ethical and practical decisions, and knowledge and inquiry tensions. The study concluded that securing institutional commitments and streamlining operational procedures are critical conditions for advancing complex, multi-partner engaged research. Additionally, guidelines to foster the development of novice educational researchers (e.g. higher degrees research students) as engaged scholars are outlined.